2020
DOI: 10.1111/ane.13304
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of non‐motor symptoms and their association with quality of life in cervical dystonia

Abstract: Despite the purely motor-related definition of cervical dystonia (CD), 1 evidence is growing that non-motor symptoms (NMS) are frequently present in CD patients and have a significant impact on the health-related quality of life (HRQoL) of these patients. 2 Depression and anxiety in particular were reported to be associated with CD and may be an intrinsic part of the CD phenotype. 3 Neuropsychiatric

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 37 publications
3
28
0
Order By: Relevance
“…MS and MS-related pain should of course be treated to improve and stabilize HR-QoL. [31][32][33][34][35] Dystonic tremor is a frequent clinical sign in dystonia 36 and tremor is a source of reduced QoL in other tremor types. 37 The impact of dystonic tremor on HR-QoL in dystonia patients has previously not been sufficiently addressed.…”
Section: Influence Of Ms and Nms On Hr-qol In Dystoniamentioning
confidence: 99%
“…MS and MS-related pain should of course be treated to improve and stabilize HR-QoL. [31][32][33][34][35] Dystonic tremor is a frequent clinical sign in dystonia 36 and tremor is a source of reduced QoL in other tremor types. 37 The impact of dystonic tremor on HR-QoL in dystonia patients has previously not been sufficiently addressed.…”
Section: Influence Of Ms and Nms On Hr-qol In Dystoniamentioning
confidence: 99%
“…In CD, the most frequent NMS are psychiatric symptoms [ 9 , 10 , 11 , 12 , 13 ], as well as sleep habit changes [ 14 , 15 , 16 ] and pain [ 17 , 18 ]. Growing evidence suggests that NMS play a pivotal role as determinants of quality of life and disability in CD patients [ 19 , 20 , 21 ], and a recent cross-sectional study has demonstrated that NMS might also intervene in determining clinical heterogeneity [ 22 ]. Finally, the relationship between motor and NMS is still a matter of debate.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the relationship between motor and NMS is still a matter of debate. Most studies have reported that NMS are independent of CD motor manifestations [ 13 , 20 , 22 ], but it has also been suggested that NMS may represent a secondary manifestation of motor burden [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of depression and anxiety were determined using a cut‐off score of ≥14 on the BDI‐II, and ≥10 on the BAI (respectively) 12 . A cut‐off score of ≥8 was used for anxiety in the HADS‐A, which has a specificity of 0.78 and a sensitivity of 0.9; a cut‐off score of ≥8 in HADS‐D has a specificity for depression of 0.79 and a sensitivity of 0.83 13 …”
Section: Methodsmentioning
confidence: 99%
“…The presence of depression and anxiety were determined using a cut-off score of ≥14 on the BDI-II, and ≥10 on the BAI (respectively). 12 A cut-off score of ≥8 was used for anxiety in the HADS-A, which has a specificity of 0.78 and a sensitivity of 0.9; a cut-off score of ≥8 in HADS-D has a specificity for depression of 0.79 and a sensitivity of 0.83. 13 Quality of Life (QoL) QoL was assessed using (1): Utility Values derived the European Quality of Life Questionnaire (EQOL-5D-5L), (2): the EQOL visual analogue score (EQOLVAS), and (3) the total CDIP-58 score.…”
Section: Mood Symptomsmentioning
confidence: 99%